Understanding the role of haptoglobin in psoriasis: effects of ultraviolet B. (1st January 2016) - Maresca, B.; Lembo, S.; Ayala, F.; Balato, N.; Di Caprio, R.; Mattii, M.; Raimondo, A.; Schiattarella, M.; Abrescia, P.; Spagnuolo, M. S.; Cigliano, L.; Balato, A.
Summary: Background: Haptoglobin (Hp) is one of the acute phase proteins, whose main function is to bind free haemoglobin (Hb) and transport it to the liver for degradation and iron recycling. In addition to its role as an Hb scavenger, Hp has been shown to behave as an anti‐inflammatory, antioxidant and angiogenic factor. We previously investigated the role of Hp in the pathogenesis of psoriasis, and found that it displays some structural modifications that might be associated with protein function in the disease. Phototherapy is an efficacious treatment for psoriasis, although the biological mechanisms by which phototherapy improves psoriasis are still unclear. Aim: To investigate the effects of ultraviolet (UV)B on Hp to clarify the role of Hp in psoriasis. Methods: Expression of the genes encoding Hp, interleukin (IL)‐6 and IL‐10 was assessed in UVB‐irradiated and unirradiated HaCaT cells. The biological significance of Hp modulation of UVB treatment was confirmed by ELISA and Western blotting. The Hp gene and protein expression in the skin of patients with psoriasis was also investigated. Results: In vitro results showed that UVB modulated IL‐6 and IL‐10 gene expression and Hp gene and protein expression in HaCaT cells. The in vivo data also showed that Hp levels were increased in the skin of patients with psoriasis compared with healthy controls. Conclusions: UVB irradiation was able to modulate Hp production in immortalized keratinocytes. The higher levels of Hp in vivo in both lesional and nonlesional skin suggest that it might have a role in the pathogenesis of the disease.